New Performance with Matrix Composites of Used Plastic, Fiber of Red Pinang Sheath and Bamboo - Nukman Nukman; qomarul hadi; Fusito Fusito (Journal of Mechanical Science and Engineering, 2013)
Ringkasan Pemanfaatan plastik bekas menjadi komposit, khususnya berbahan plyproplene (PP) telah dapat dilakukan dengan cara menambahkan serat Bambu dan Pelepah Pinang Merah. Matriks PP dipanaskan dalam satu alat pemanas untuk dicairkan kemudian ditambahkan masing-masing serat alam bambu dan juga pinang merah. Hasil pengujian sifat mekanik telah dibandingkan matriks tanpa penambahan serat dengan matriks yang berserat. Pengujian menujukkan bahwa sifat mekanik dari kompisit telah meningkat dengan penambahan serat alami. Kekuatan mekanik dengan penambahan serat bambu lebih besar daripada penambahan dengan serat Pinang Merah. Kata Kunci: Polyproplene, serat Bambu, serat Pinang Merah, Komposit, Kekuatan Mekanik. Utilization of scrap plastic to composite, especially made ​​plyproplene (PP) has to be done by adding fibers and sheaths Pinang Red Bamboo. PP matrix is heated in the heater melted then added to each of the natural bamboo fiber and red nut. Mechanical properties of the test results have been compared with the fiber-matrix without the addition of a fibrous matrix. Tests showed that the mechanical properties of kompisit has increased with the addition of natural fibers. Mechanical strength with the addition of bamboo fiber is greater than the addition of the Red Pinang fiber. Keywords : polyproplene, Bamboo fiber, fiber Pinang Merah, Composite, Mechanical Strength.